Determination of trace amounts of selenium in natural spring waters and tea samples by catalytic kinetic spectrophotometry - Gürkan, Ramazan; Gürkan, Nevalnur Zeynep (Eclética Química, 2019)
In this work, a new kinetic method is described for the determination of trace Se(IV) in natural spring waters and commercial tea samples. The method is based on the activation of Se(IV) onto the indicator reaction in acidic medium. The reaction was monitored using a fixed time approach of 20 min at 680 nm. The variables affecting the reaction rate were evaluated and optimized. The method allows the determination of Se(IV) in the range of 0.0125-1.0 mg L-1 with a detection limit of 3.6 µg L-1. The precision was in range of 0.63-3.15% (as RSD %) with a higher recovery than 98.6%. The method has been found to be selective against matrix effect. The method was applied to the speciation analysis of inorganic Se species present in the selected samples. The method was statistically validated by analysis of two certified samples and comparing the obtained results to those of HG-AAS analysis. Also, the total Se levels of the samples were determined by using both methods after conversion of Se(VI) into Se(IV) in ultrasonic bath in acidic medium for 30 min at 85-90 °C. The results were in good agreement with those of HG-AAS. The Se(VI) level of the samples was calculated from the difference between amounts of total Se and Se(IV).